Thu gọn biểu thức sau :
a) 2(x+1)+3x
b) (x+2)2-x(x+3)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,B=x^2+x-2-x^2+2x-3x=-2\\ b,B=\left(x^3-3x^2+3x-1\right)+1021=\left(x-1\right)^3+1021\\ B=\left(11-1\right)^3+1021=1000+1021=2021\)
\(a,=27-5\sqrt{3x}\\ b,=3\sqrt{2x}-10\sqrt{2x}+21\sqrt{2x}+28=14\sqrt{2x}+28\)
a: A(x)=3x^3+3x-1
B(x)=-2x^3+x^2+4x-3
b: A(x)+B(x)
=3x^3+3x-1-2x^3+x^2+4x-3
=x^3+x^2+7x-4
B(x)-A(x)
=-2x^3+x^2+4x-3-3x^3-3x+1
=-5x^3+x^2+x-2
c; M(x)=x^3+x^2+7x-4
M(-3)=-27+9-21-4=-31-21+9=-43
a.ta có
\(\left(x+3\right)^3+\left(x^2+1\right)\left(x-2\right)=x^3+9x^2+27x+27+x^3-2x^2+x-2\)
\(=2x^3+7x^2+28x+25\)
b.\(\left(2x-1\right)^2-\left(2-x\right)^3=4x^2-4x+1+x^3-6x^2+12x-8\)
\(=x^3-2x^2+8x-7\)
a) (x + 3)3 + (x2 + 1)(x - 2)
= x3 + 9x2 + 27x + 27 + x3 - 2x + x - 2
= x3 + x3 + 9x2 + 27x - 2x + x + 27 - 2
= 2x3 + 9x2 + 26x + 25
b) (2x - 1)2 - (2 - x)3
= 4x2 - 4x + 1 - ( 8 - 12x + 6x2 - x3)
= 4x2 - 4x + 1 - 8 + 12x - 6x2 + x3
= x3 + 4x2 - 6x2 + 12x - 4x + 1 - 8
= x3 - 2x2 + 8x - 7
A = (x - 1)3 - x(x - 2)2 + 1
A = (x - 1)(x2 - 2x + 1) - x(x - 2)2 + 1
A = x(x2 - 2x + 1) - (x2 - 2x + 1) - x(x - 2)2 + 1
A = x3 - 2x2 + x - (x2 - 2x + 1) - x(x2 - 2x.2 + 22) + 1
A = x3 - 2x2 + x - (x2 - 2x + 1) - (x3 - 4x2 + 4x) + 1
A = x3 - 2x2 + x - x2 + 2x - 1 - x3 + 4x2 - 4x + 1
A = (x3 - x3) + (-2x2 - x2 + 4x2) + (x + 2x - 4x) + (-1 + 1)
A = x2 - x
B = (-x - 2)3 + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = (-x - 2)[(-x2) - 2.(-x).2 + 22] + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = -x[(-x)2 - 2.(-x).2 + 22] - 2[(-x)2 - 2.(-x).2 + 22] + (2x - 4)(x2 + 2x + 4) - x2(x - 6)
B = -(x3 + 4x2 + 4x) - (2x2 + 4x + 8) + 2x(x2 + 2x + 4) - 4(x2 + 2x + 4) - x2(x - 6)
B = -(x3 + 4x2 - 4x) - (2x2 + 4x + 8) + 2x3 + 4x2 + 8x - (x2 + 8x + 16) - (x3 - 6x2)
B = -x3 - 4x2 + 4x - 2x2 - 4x - 8 + 2x3 + 4x2 + 8x - x2 - 8x - 16 - x3 + 6x2
B = (-x3 + 2x3 - x3) + (-4x2 - 2x2 + 4x2 - x2 + 6x2) + (-4x - 8x + 8x - 8x) + (-8 - 16)
B = -12x - 24
a ) 2 ( x + 1 ) + 3x = 2x + 2 + 3x = 5x + 2
b ) (x+2)2-x(x+3) = ( x2 + 4x + 4 ) - ( x2 + 3x ) = x + 4
a, 2(x + 1) + 3x
= 2x + 2 + 3x
= 5x + 2
b, (x + 2)2 - x(x + 3)
= x2 + 4x + 4 - x2 - 6x - 9
= - 2x - 5